Impact on Financial Decisions through Resources and Education - Mane, Dr. Pallavi; Wisetsri, Worakamol; Gupta, Shashi Kant (The journal of contemporary issues in business and government, 2021)
In high stakes financial decisions, people leave a substantial amount of money on the table, even when financial education is available. The ubiquity of financial choices makes understanding the effects of incentives and education on mistakes crucial. This research experimentally examines the impact of changes in incentives and educational availability on incentivized but hypothetical healthcare choices using Amazon Mechanical Turk. We find that increasing incentives are ineffective in increasing decision-making effort, even when these changes are made clear and salient to the subjects. Yet, surprisingly, despite this lack of effort response, subjects’ choices improve when incentives are high. This result highlights an under-appreciated channel of incentives: when stakes become larger, often, the problems become simpler too. We next investigate the effect of available education. Overall, education leads to an increase in decision-making effort and an improvement in choice quality. However, this average effect masks significant heterogeneity across incentive treatments. Subjects are willing to put in the educational effort when either the problems are hard or mistakes are highly costly, but the return of the educational effort is zero for hard problems and positive for easy ones. Thus, only when stakes are high and the problem is easy, does education have an effect. These findings suggest that people can be encouraged to get education for high-stakes decisions, and policy-makers have a role in simplifying problems to translate the extra effort into better choices.